Review of Implementation of the Village Developmental Framework's Functions According to Participatory Principles for Developing Village Democracy (Study in Sukopuro Village, Jabung District, Malang Regency) - Soleh, Mukhammad; Putra, Marsudi Dedi; Novitasari, Rika; Bagijo, Himawan Estu; Maharani, Devita Alya; Aryanti, Dia Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The principles of good governance must guide the Village Government's and the Village Consultative Body's implementation of Village Government. The village consultative frame's activities include directing and accommodating the village network's goals, reviewing the proposed community rule with the village head, and keeping tabs on the village head's overall performance. The research method used is empirical juridical, sociological juridical approach, primary data collection method using interviews and observation, secondary data collection method through literature study and data analysis using sociological juridical analysis through stages of data presentation, data reduction and conclusion drawing. The research results show that the application of participatory principles in implementing the functions of the Village Consultative Body has gone well. However, there are still shortcomings, namely the lack of quality human resources from members of the Village Consultative Body and the Village community. There is still a lack of facilities and infrastructure from the Village Consultative Board for publishing programs and activities